Targeted unlabeled multiple reaction monitoring analysis of cell markers for the study of sample heterogeneity in isolated rat brain cortical microvessels. Issue 4 (11th July 2017) - Gomez‐Zepeda, David; Chaves, Catarina; Taghi, Méryam; Sergent, Philippe; Liu, Wang‐Qing; Chhuon, Cérina; Vidal, Michel; Picard, Martin; Thioulouse, Elizabeth; Broutin, Isabelle; Guerrera, Ida‐Chiara; Scherrmann, Jean‐Michel; et al.
Abstract: Liquid chromatography coupled to tandem mass spectrometry‐based targeted absolute protein quantification (in fmol of the analyte protein per μg of total protein) is employed for the molecular characterization of the blood–brain barrier using isolated brain microvessels. Nevertheless, the heterogeneity of the sample regarding the levels of different cells co‐isolated within the microvessels and bovine serum albumin (BSA) contamination (from buffers) are not always evaluated. We developed an unlabeled targeted liquid chromatography coupled to tandem mass spectrometry method to survey the levels of endothelial cells (ECs), astrocytes, and pericytes, as well as BSA contaminant in rat cortical microvessels. Peptide peak identities were evaluated using a spectral library and chromatographic parameters. Sprague–Dawley rat microvessels obtained on three different days were analyzed with this method complemented by an absolute quantification multiple reaction monitoring method for transporter proteins P‐gp, Bcrp, and Na + /K + ATPase pump using stable isotope labeled peptides as internal standard. Inter‐day differences in the cell markers and BSA contamination were observed. Levels of cell markers correlated positively between each other. Then, the correlation between cell marker proteins and transporter proteins was evaluated to choose the best EC marker protein for protein quantification normalization. The membrane protein Pecam‐1 showed a very high correlation with the EC‐specific transporter P‐gp (Pearson product‐moment correlation coefficient ( r ) > 0.89) and moderate to high with Bcrp ( r ≥ 0.77), that can be found also in pericytes and astrocytes. Therefore, Pecam‐1 was selected as a marker for the normalization of the quantification of the proteins of endothelial cells. Abstract : An unlabeled targeted LC‐MRM (MS/MS) method was used to survey the enrichment levels of endothelial cells, astrocytes, and pericytes, as well as BSA contaminant in protein samples from rat cortical microvessels. The endothelial cell marker Pecam‐1 showed high correlation with ABC transporters, P‐gp and Bcrp (quantified using stable isotope labeled peptides), and was validated as a marker for protein amount normalization.